Free Gingival Graft and Collagen Matrix Revascularization in an Enoral Open Wound Situation - Preidl, Raimund; Reichert, Sky Helen; Vallenas Coronel, Talisa; Kesting, Marco Rainer; Wehrhan, Falk; Schmitt, Christian (Journal of Oral and Maxillofacial Surgery, 2021)
Purpose: Vestibuloplasty with free gingival grafting is a frequently performed surgical procedure to generate sufficient keratinized mucosa (KM) around dental implants. Avascular porcine collagen matrices (CM) have been proclaimed to be sufficient substitutes as alternatives to free gingival grafts (FGGs). However, the process of graft integration and vascularization is still incompletely understood. Methods: In 18 patients a vestibuloplasty in the lower edentulous jaw situation was performed during implant exposure, either with FGGs from the palate or a porcine CM (mucoderm). Tissue perfusion of the soft tissue grafts was measured using laser-doppler-spectrophotometer intraoperatively and on postoperative days 2, 5, 10, 30 and between days 60 and 90. With graft perfusion expressed by oxygen saturation [SO2%], the relative amount of hemoglobin [rHb], blood flow, and velocity [AU] was detected and compared between groups and the surrounding mucosa. Results: Healing was uneventful in both groups, with mature KM around dental implants after healing. Blood flow and velocity significantly increased until postoperative day 10, comparable to perfusion values of the surrounded mucosa. Intergroup comparisons revelated no significant differences concerning the flow between CM and FGGs. Oxygen saturation also significantly increased within the first 5 postoperative days in both groups. Hemoglobin content did not show any differences during the investigated period. Conclusions: The perfusion mainly progresses within the first postoperative week with only minimal further detectable alterations until the final investigation, comparable in both groups. Although integration of FGGs (revascularized) and the CM (new tissue formation) is biologically different, both transplants show comparable perfusion patterns, leading to sufficient KM.
CRIS-Team Scopus Importer:2021-04-19